2020
DOI: 10.1007/s12671-020-01325-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion as a Stress Moderator: A Cross-sectional Study of 1700 Doctors, Nurses, and Medical Students

Abstract: Objectives Work stress is common in healthcare and reliably predicts negative outcomes, including burnout and lower quality of life (QOL). However, few studies have investigated factors that might attenuate the impact of stress on these negative outcomes. We investigated whether the tendency to be kind to the self during times of difficulty-self-compassion-might buffer the effect of work stress on outcomes. Methods Registered nurses (n = 801), physicians (n = 516), and medical students (n = 383) were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 85 publications
4
46
1
1
Order By: Relevance
“…Eby and colleagues’ (2019) review showed that individuals who most benefited from mindfulness training and its related outcomes, like self-compassion, were those who experienced higher levels of stress. Additionally, they reported that mindfulness trainings were beneficial for individuals who were employed in jobs that have high demands, such as the military and police, practicing psychologists (Eriksson et al, 2018), healthcare workers (Dev et al, 2020; Vaillancourt & Wasylkiw, 2019), and women managers from the cosmetics sector (Pires et al, 2018).…”
Section: A Practical Guide To Nurture Workplace Self-compassionmentioning
confidence: 99%
“…Eby and colleagues’ (2019) review showed that individuals who most benefited from mindfulness training and its related outcomes, like self-compassion, were those who experienced higher levels of stress. Additionally, they reported that mindfulness trainings were beneficial for individuals who were employed in jobs that have high demands, such as the military and police, practicing psychologists (Eriksson et al, 2018), healthcare workers (Dev et al, 2020; Vaillancourt & Wasylkiw, 2019), and women managers from the cosmetics sector (Pires et al, 2018).…”
Section: A Practical Guide To Nurture Workplace Self-compassionmentioning
confidence: 99%
“…In Iran, more than 75% of nurses suffer from stress, depression and other mental problems that have a detrimental effect on their own and their patients' lives (Aghilinejad et al, 2010). The relationship between stress and burnout in nurses has been investigated in several studies (Dev et al, 2020;Kim, 2020;Montanari et al, 2019;Pe´rula-de Torres et al, 2019;Wang et al, 2020). However, limited studies have shown a relationship between perceived stress and job burnout in nurses (Divinakumar et al, 2014;Mahon et al, 2017;Munnangi et al, 2018), and the relationship between perceived stress and burnout has not been studied among Iranian nurses.…”
Section: Introductionmentioning
confidence: 99%
“…The high burnout rates among future doctors are often related to contextual factors inherent to their professional environment (Dev, Fernando and Consedine, 2020). Dutch medical training is characterized by a high work intensity due to heavy patient loads and long, irregular working days (Van Esch and Soomers, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies, however, investigated these associations between self-compassion, well-being and performance in the setting of medical education. Dev, Fernando and Consedine (2020) recently found that greater self-compassion predicted lower burnout and better quality of life in a sample of 383 medical students, with female students reporting lower levels of self-compassion. In a smaller sample of paediatric residents, self-compassion was positively associated with resilience (Olson, Kemper and Mahan, 2015).…”
Section: Introductionmentioning
confidence: 99%